Asymmetric polyoxometalate electrolytes for advanced redox flow batteries. Issue 10 (10th August 2018) - Friedl, Jochen; Holland-Cunz, Matthäa V.; Cording, Faye; Pfanschilling, Felix L.; Wills, Corinne; McFarlane, William; Schricker, Barbara; Fleck, Robert; Wolfschmidt, Holger; Stimming, Ulrich
Abstract : A redox flow battery using two polyoxometalate electrolytes for anolyte and catholyte is described and investigated. Abstract : Electrochemical storage of energy is a necessary asset for the integration of intermittent renewable energy sources such as wind and solar power into a complete energy scenario. Redox flow batteries (RFBs) are the only type of battery in which the energy content and the power output can be scaled independently, offering flexibility for applications such as load levelling. However, the prevailing technology, the all Vanadium system, comprises low energy and low power densities. In this study we investigate two polyoxometalates (POMs), [SiW12 O40 ] 4− and [PV14 O42 ] 9−, as nano-sized electron shuttles. We show that these POMs exhibit fast redox kinetics (electron transfer constant k 0 ≈ 10 −2 cm s −1 for [SiW12 O40 ] 4− ), thereby enabling high power densities; in addition, they feature multi-electron transfer, realizing a high capacity per molecule; they do not cross cation exchange membranes, eliminating self-discharge through the separator; and they are chemically and electrochemically stable as shown by in situ NMR. In flow battery studies the theoretical capacity (10.7 A h L −1 ) could be achieved under operating conditions. The cell was cycled for 14 days with current densities in the range of 30 to 60 mA cm −2 (155 cycles). The Coulombic efficiency was 94% during cycling. Very small losses occurred due to residual oxygen in the system. The voltage efficiency (∼65% at 30 mA cm −2 ) was mainly affected by ohmic rather than kinetic losses. Pathways for further improvement are discussed.